Enzyme-Photocatalyst Tandem Microrobot Powered by Urea for Escherichia coli Biofilm Eradication - Villa, Katherine; Sopha, Hanna; Zelenka, Jaroslav; Motola, Martin; Dekanovsky, Lukas; Beketova, Darya Chylii; Macak, Jan M; Ruml, Tomáš; Pumera, Martin (Small (Weinheim an der Bergstrasse, Germany), 2022)
Urinary-based infections affect millions of people worldwide. Such bacterial infections are mainly caused by Escherichia coli (E. coli) biofilm formation in the bladder and/or urinary catheters. Herein, the authors present a hybrid enzyme/photocatalytic microrobot, based on urease-immobilized TiO2 /CdS nanotube bundles, that can swim in urea as a biocompatible fuel and respond to visible light. Upon illumination for 2 h, these microrobots are able to remove almost 90% of bacterial biofilm, due to the generation of reactive radicals, while bare TiO2 /CdS photocatalysts (non-motile) or urease-coated microrobots in the dark do not show any toxic effect. These results indicate a synergistic effect between the self-propulsion provided by the enzyme and the photocatalytic activity induced under light stimuli. This work provides a photo-biocatalytic approach for the design of efficient light-driven microrobots with promising applications in microbiology and biomedicine.
Keywords: enzymatic; urinary infections; micromotors; titan; Titanium; Escherichia coli; TiO 2 nanotubes; ureasa; Robotics; bacterial biofilms; photocatalysis; Urease; lidé; Biofilms; robotika; Humans; močovina; Catalysis; Urea; biofilmy; katalýza